‘The Figure of the Old with the Pathetic Tenderness of the New’: An Early Reading of Sterne’s A Sentimental Journey (1768) - Daniel Reed (Humanities)
This essay introduces the Reed ASJ as a new primary source for the early reception of Laurence Sterne’s second novel, A Sentimental Journey Through France and Italy (1768) and draws on recent developments in marginalia studies to locate it within its contemporary historical context. This framework informs discussion of the reader’s possible identity, their use of annotation, and wide-ranging responses to the novel such as comparative readings with Tristram Shandy (1759–1767), assessments of Sterne’s religiosity, and the depiction of French society and customs. Also explored are the reader’s strong interventions with passages in the novel that were beneath their expectations. And so, the recovery of the Reed ASJ suggests fresh possibilities for the reinvestigation of ASJ’s inherent paradoxes, its disputed sincerity in the sentimental mode and relationship to genre that fuel the novel’s ongoing popularity.